Climatic variation modulates the indirect effects of large herbivores on small‐mammal habitat use. (2nd May 2017) - Long, Ryan A.; Wambua, Alois; Goheen, Jacob R.; Palmer, Todd M.; Pringle, Robert M.
Summary: Large mammalian herbivores (LMH) strongly shape the composition and architecture of plant communities. A growing literature shows that negative direct effects of LMH on vegetation frequently propagate to suppress the abundance of smaller consumers. Indirect effects of LMH on the behaviour of these consumers, however, have received comparatively little attention despite their potential ecological significance. We sought to understand (i) how LMH indirectly shape small‐mammal habitat use by altering the density and distribution of understorey plants; (ii) how these effects vary with climatic context (here, seasonality in rainfall); and (iii) the extent to which behavioural responses of small mammals are contingent upon small‐mammal density. We tested the effects of a diverse LMH community on small‐mammal habitat use using 4 years of spatially explicit small‐mammal trapping and vegetation data from the UHURU Experiment, a replicated set of LMH exclosures in semi‐arid Kenyan savanna. Small‐mammal habitat use was positively associated with tree density and negatively associated with bare (unvegetated) patches in all plots and seasons. In the presence of LMH, and especially during the dry season, small mammals consistently selected tree cover and avoided bare patches. In contrast, when LMH were excluded, small mammals were weakly associated with tree cover and did not avoid bare patches as strongly. These behavioural responses of small mammals were largely unaffected by changes in small‐mammal density associated with LMH exclusion. Our results show that LMH indirectly affect small‐mammal behaviour, and that these effects are influenced by climate and can arise via density‐independent mechanisms. This raises the possibility that anthropogenic LMH declines might interact with changing patterns of rainfall to alter small‐mammal distribution and behaviour, independent of numerical responses by small mammals to these perturbations. For example, increased rainfall in East Africa (as predicted in many recent climate‐model simulations) may relax constraints on small‐mammal distribution where LMH are rare or absent, whereas increased aridity and/or drought frequency may tighten them. Abstract : This study of a large herbivore → plant → small consumer interaction pathway in central Kenya provides some of the first experimental evidence that large herbivores and climate interactively influence behaviour of smaller‐bodied consumers, and that density‐independent shifts in behaviour likely play a critical role in governing ecological processes.